Nonselective versus selective His bundle pacing: An acute intrapatient speckle-tracking strain echocardiographic study - Bednarek, Agnieszka; Ionita, Oana; Moskal, Paweł; Linkova, Hana; Kiełbasa, Grzegorz; Prochazkova, Radka; Vesela, Jana; Rajzer, Marek; Curila, Karol; Jastrzębski, Marek (Journal of cardiovascular electrophysiology, 2021)
INTRODUCTION: We aimed to compare the acute differences in left ventricular (LV) function and mechanical synchrony during nonselective His bundle pacing (ns-HBP) versus selective His bundle pacing (s-HBP) using strain echocardiography. METHODS AND RESULTS: Consecutive patients with permanent His bundle pacing, in whom it was possible to obtain both s-HBP and ns-HBP, were studied in two centers. In each patient, echocardiography was performed sequentially during s-HBP and ns-HBP. Speckle-tracking echocardiography parameters were analyzed: Global longitudinal strain (GLS), the time delay between peak systolic strain in the basal septal and basal lateral segments (BS-BL delay), peak strain dispersion (PSD) and strain delay index. Right ventricle function was assessed using tricuspid annular plane systolic excursion (TAPSE) and tissue Doppler velocity of the lateral tricuspid annulus (S'). A total of 69 patients (age: 75.6 ± 10.5 years; males: 75%) were enrolled. There were no differences in LV ejection fraction and GLS between s-HBP and ns-HBP modes: 59% versus 60%, and -15.6% versus -15.7%, respectively; as well as no difference in BS-BL delay and strain delay index. The PSD value was higher in the ns-HBP group than in the s-HBP group with the most pronounced difference in the basal LV segments. No differences in right ventricular function parameters (TAPSE and S') were found. CONCLUSION: The ns-HBP and s-HBP modes seem comparable regarding ventricular function. The dyssynchrony parameters were significantly higher during ns-HBP, however, the difference seems modest and clarification of its impact on LV function requires a larger long-term study.
Keywords: Stroke Volume; nonselective His bundle pacing; Cardiac Pacing, Artificial; Male; kardiostimulace umělá; funkce pravé komory srdeční; Ventricular Function, Right; Aged; Echocardiography; mužské pohlaví; senioři; tepový objem; echokardiografie; dyssynchrony; speckle strain echocardiography; lidé; Humans; Bundle of His; selective His bundle pacing; Hisův svazek; left ventricular function